Analysis of the Process of Encoding Guidelines: A Comparison of GLIF2 and GLIF3 - Patel, V. L.; Branch, T.; Wang, D.; Peleg, M.; Boxwala, A. (Methods of Information in Medicine, 2002)
Objectives: This study aims to evaluate the use of a modified version of the Guideline Interchange Format (GLIF), GLIF3, in the translation of clinical practice guidelines into an electronically encoded form such that they may be shared among various clinical institutions and settings.Methods: Based on theories and methods from cognitive science, the encoding of two clinical practice guidelines into two guideline modeling methods (GLIF3 and an earlier version, GLIF2) by two medical informaticians was captured on video and transcribed and annotated for analysis.Results: Differing in both content and structure, the representations developed in GLIF3 were found to contain a greater level of representational detail and less ambiguity than those developed in GLIF2.Conclusions: The use of GLIF3 in the encoding of clinical guidelines offers significant improvements due to its greater formality as compared to earlier versions of GLIF.
Keywords: Knowledge; practice guidelines; evaluation studies; cognitive science